A Study on Work Life Balance among Working Women with Special Reference to Coimbatore District - Shammine, Ms. G Lourds; R, Ms.Boomika. (International Journal of Scientific Research and Management (IJSRM), 2023)
Work-life balance is an important part of any company's employees, as emphasis is placed on the balance between personal and professional life. Based on work-life balance, working women can organize their personal and work lives more efficiently and effectively. This research is based on work-life balance, which is essential to combating stress and ensuring both individual and organizational success. Work-life balance is about making time each day for family, friends, community involvement, holiness, personal growth, self-care, and other personal activities in addition to the challenges of the workplace. This study employed a descriptive research design and purposive sampling technique. A sample size of 60 people was collected using a questionnaire. The survey concludes that (57%) of respondents have a moderate work-life balance. 18% of those surveyed have a poor work-life balance. 25% of those surveyed had a good work-life balance